Methyl and dimethyl o-xylenyl-substituted fullerene acceptors for polymer solar cells - Kim, Hee Un (2015)
A series of fullerene derivatives based on methyl- and dimethyl-substituted o-xylenyl groups were synthesized via Diels-Alder reaction from fullerene (C60) and dienes derived from α,α′-dibromo-o-xylene derivatives. The synthesized 1-methyl-4,5-xylenyl- and 1,2-dimethyl-4,5-xylenyl-substituted fullerene mono-, bis-, and trisadducts, i.e., M_OXCMA, M_OXCBA, M_OXCTA, DM_OXCMA, DM_OXCBA, and DM_OXCTA, were used as electron-acceptor materials for polymer solar cells and have good solubility in common organic solvents. The Stern-Volmer quenching constants for poly(3-hexylthiophene) (P3HT) as a fluorophore with M_OXCMA, M_OXCBA, M_OXCTA, DM_OXCMA, DM_OXCBA, and DM_OXCTA as quenchers were 1.35×104, 7.67×103, 3.72×103, 1.38×104, 7.95×103, and 4.10×103 M−1, respectively. These values correlate with the binding affinities of the fluorophore and quencher. The lowest unoccupied molecular orbital energy levels increased with increasing number of adducts on the fullerene because of their decreasing number of sp2-hybridized carbons. Photovoltaic devices were fabricated using P3HT and the mono-, bis-, and trisadducts as electron donors and acceptors, respectively. Among these, the cells with an ITO/PEDOT : PSS/P3HT : DM_OXCBA/LiF/Al structure had the highest power conversion efficiency of 4.77 % with an open-circuit voltage of 0.88 V, a short-circuit current density of 10.52 mA cm−2, and a fill factor of 0.51 under AM 1.5G (100 mW cm−2) illumination.